From Religion to Civilisation: A Study of Muhyar Fanani's Thoughts on The Reorientation of Ushuluddin Studies - Elitdwitia Elitdwitia; Ahmad Bayhaqy; Rakhmah Andini; Eka Martita Indah; Faqih Aly Ridho; Fitriani Fitriani; Nabila Rizqi Setiyoningsih (International Tatho Academics, 2026)
This study aims to describe the thoughts of Muhyar Fanani, a professor of Islamic law in Indonesia, regarding the reorientation of Ushuluddin studies to be more contextual with contemporary social realities. This study uses a qualitative method with a literature review approach. The results of the study show that Muhyar Fanani views the reorientation of Ushuluddin as requiring a radical, in-depth, and integrative approach between religious texts and social realities, particularly through dialogue between religion and science and responses to social change through contextual ijtihad. Theoretically, this study emphasises the importance of an integrative paradigm in bridging revelation and reason amid the dominance of modern science.